KAJIAN AWAL PEMANFAATAN PULP DARI LIMBAH KEMASAN ASEPTIK UNTUK PEMBUATAN SELULOSA ASETAT - Khadafi, Mahammad; Kencana, Yuniarti P. (Center for Pulp and Paper, 2013)
The use of aseptic packaging in the world is still increasing from year to year, this causes a new matter like midden. Recycling the aseptic packaging is one of the efforts to utilize this waste. The raw material used for cellulose acetate crystal can be obtained from recycling process of aseptic packaging waste. This can be possible because pulp from aseptic packaging contain 72% needle unbleached virgin pulp. The purpose of this reasearch is to diversify the use of aseptic packaging waste by improving the technology process of acetylation for making cellulose acetate crystal. Aseptic packaging pulp was tested for the parameters such as water content, ash content, holocellulose content, Î±-cellulose content, lignin content, and hemicellulose content. This tested was used to know the eligibility of pulp for making cellulose acetate. The pulp was soaked with water and glacial acetic acid for swelling and conditioning. The acetylation process was done with adding glacial acetic acid and acetic acid anhydride in certain composition. Based on ASTM D 871-96 testing method, we obtained the optimum condition of acetyl content is 36.85% by adding 2.25 mL water and 35 mL acetic acid anhydride, whereas with the addition of 2.75 mL water and 30 mL acetic acid anhydride 28.28% acetyl content were obtained.Keywords : aseptic packaging pulp, acetate cellulose, acetylation process, acetyl contentÂ Â ABSTRAKPenggunaan kemasan aseptik yang meningkat dari tahun ke tahun, menimbulkan masalah baru berupa limbah. Salah satu upaya pemanfaatan limbah adalah melalui proses daur ulang. Hasil proses daur ulang ini diantaranya dapat dijadikan substitusi bahan baku produk derivat selulosa berupa selulosa asetat, karena limbah kemasan aseptik mengandung pulp virgin serat panjang 72%. Tujuan dari penelitian ini adalah untuk diversifikasi penggunaan dan pemanfaatan limbah kemasan aseptik melalui proses daur ulang dan penguasaan teknologi proses asetilasi untuk produk selulosa asetat. Pulp kemasan aseptik diuji dengan parameter kadar air, kadar abu, kadar holoselulosa, kadar Î± selulosa, kadar lignin, dan kadar hemiselulosa untuk mengetahui apakah pulp kemasan aseptik memenuhi persyaratan untuk dibuat selulosa asetat. Perendaman pulp dilakukan dengan air dan asam asetat glasial, kemudian diperas untuk mengkondisikan pulp sebelum proses asetilasi. Proses asetilasi dilakukan dengan menambahkan asam asetat glasial dan asam asetat anhidrida dalam jumlah tertentu. Berdasarkan metode ASTMD 871-96 diperoleh kadar asetil optimal dari kristal selulosa asetat sebesar 36,85% dengan penambahan air 2,25 mL dan asetat anhydrida 35 ml, sedangkan untuk penambahan asam asetat anhidrida 30 mL dan air 2,75 mL diperoleh kadar asetil 28,28%.Kata kunci : pulp kemasan aseptik, selulosa asetat, asetilasi, kadar asetil